Spoligotyping, phenotypic and genotypic characterization of katG, rpoB gene of M. tuberculosis isolates from Sahariya tribe of Madhya Pradesh India - Rahul Gupta; Rabbind Singh Amrathlal; Ravi Prakash; Sanjay Jain; Pramod K. Tiwari (Elsevier, 2019)
Background: Sahariya, a primitive tribal group, residing in Gwalior and Sheopur districts of Madhya Pradesh, India, show high incidence and prevalence of pulmonary tuberculosis (PTB). The study was designed to understand the genetic diversity and phenotype - genotype association of drug resistant M. tuberculosis strains, infecting Sahariya tribe. Materials and methods: A total of 103 pulmonary tuberculosis patients from Sahariya tribe were recruited from Gwalior and Sheopur districts. Sputum samples were collected and cultured on LJ slants and drug sensitivity tests were carried out. Genomic DNA was extracted, followed by spoligotyping and genotyping of drug target genes, katG and rpoB, using MAS-PCR, PCR-RFLP and DNA sequencing. Result: Seventeen different spoligotypes were identified, in which, EAI3_IND/ST11 M. tuberculosis strain appeared predominant, followed by CAS1_Delhi/ST26. Results of our phenotypic drug susceptibility test identified high incidence (12.6%) of isoniazid-resistant tuberculosis, while 4.85% isolates were multi drug resistant (MDR). Further genotyping of drug target genes identified 8.7% of isoniazid-R isolates to have a mutation at katG codon 463, while 3.8% isolates showed mutations at two sites, katG codons 315 and 463. In case of MDR-TB isolates, all from CAS lineage, 3.85% had mutations on katG and rpoB genes, at codon 463 and codon 526, respectively, while 0.97% isolates were harbouring mutations at codons 315, 463 and 531. Conclusion: Our findings have revealed that EAI3_IND strain is the predominant strain infecting Sahariya. The incidence of isoniazid-R M. tuberculosis strain infection is high, with an increased propensity to evolve into MDR-TB. Therefore, the TB centres should also consider isoniazid-R status of the isolates along with CBNAAT before deciding the drug regimen for the patients. Keywords: Isoniazid resistance, Multi-drug resistance, M. tuberculosis, Sahariya tribe, Spoligotyping